Perancangan Sistem Informasi Pengawasan Penyidikan Berbasis Web Pada DITRESKRIMSUS POLDA DIY - Gunawan Budi Sulistyo; Heny Widayati UBSI (APMMI - Asosiasi Profesi Multimedia Indonesia, 2020)
Abstrak Investigation Supervision aims to assist the Director of Special Criminal Investigations in overseeing the investigation process in order to minimize errors / mistakes and maximize the quality and speed of the investigation process. Improving services to the community in accordance with the National Police Chief Bureaucracy Reform (Quick Wins) program that has been published to the public through a transparent and accountable investigation process. The use of a system that is still manual in the collection and processing of case data is an obstacle in realizing this goal, due to the lack of IT-based infrastructure and innovations in the investigation surveillance system in the Indonesian National Police. So this research was conducted to find innovations in designing the information system of investigation oversight at the Directorate of Special Criminal Investigation of the Regional Police D.I. Yogyakarta. The goal is not only Bagwassidik who uses this system, but other bags and bags like Bagbinops, Subbagrenmin and Banum Subdit can also use this system, of course, by developing systems that are tailored to the needs. It is hoped that with this system it will be easier to collect case data, find out case developments and find out where the investigator's performance in handling a case. The Design of Information Systems for Investigation Oversight is made using the Prototype model as its software development model. The results of this study are a prototype of the information surveillance surveillance monitoring system that is suitable for the intended user system. Keywords : Design, Information System, Investigation, Supervision, prototype Abstrak – Pengawasan Penyidikan bertujuan untuk membantu Direktur Reserse Kriminal Khusus dalam mengawasi proses penyidikan guna meminimalisir kesalahan/kekeliruan dan memaksimalkan kualitas serta kecepatan dalam proses penyidikan. Meningkatkan pelayanan kepada masyarakat sesuai dengan program Kapolri Reformasi Birokrasi (Quick Wins) yang telah dipublikasikan kepada masyarakat melalui proses penyidikan yang transparan dan akuntabel. Penggunaan sistem yang masih manual pada pengumpulan dan pengolahan data perkara menjadi kendala dalam mewujudkan tujuan tersebut, dikarenakan kurangnya sarana prasarana serta innovasi yang berbasis IT pada pada Sistem Pengawasan penyidikan yang ada di Polri. Sehingga penelitian ini dilakukan untuk menemukan inovasi dalam merancang sistem informasi pengawasan penyidikan pada Direktorat Reserse Kriminal Khusus Polda D.I. Yogyakarta. Tujuannya tidak hanya Bagwassidik saja yang menggunakan sistem ini, Namun Subbag dan Bag lain seperti Bagbinops, Subbagrenmin dan Banum Subdit juga dapat menggunakan sistem ini tentunya dengan pengembangan sistem yang disesuaikan dengan kebutuhan. Diharapkan dengan adanya sistem ini akan lebih mudah dalam mengumpulkan data perkara, mengetahui perkembangan perkara dan mengetahui sampai dimana kinerja penyidik dalam menangani suatu perkara. Perancangan Sistem Informasi Pengawasan Penyidikan dibuat dengan model Prototype sebagai model pengembangan perangkat lunaknya. Hasil dari penelitian ini adalah sebuah prototype sistem perangcangan informasi pengawasan penyidikan yang sesuai dengan alur dan sistem yang dikehendaki oleh calon pengguna. Kata kunci: Perancangan, Sistem Informasi, Pengawasan Penyidikan, prototype